The effect of small sided games with the principles of interval, pyramid, mix on increasing VO2max and Teamwork of football players - Fadli, Muhamad; Mahendra, Agus; Rusdiana, Agus; Sholehudin, Indra (Jorpres (Jurnal Olahraga Prestasi), 2024)
Athlete performance will always be side by side with physical condition because football is included in the complex achievement sport in its game which does not only rely on technical and tactical abilities but must be supported by a fit physical condition, therefore physical condition is a necessity in improving an athlete's performance, it can even be considered a basic need that cannot be postponed or negotiated. Football itself is a team game, where in the game it cannot be played alone and do not let egoism or individual play become a character. The purpose of this study was to determine the comparison of the effect of differences in increasing VO2Max and Teamwork by applying the principles of endurance training such as intervals and pyramids, as well as the principle of combining the two principles called mix. This research was conducted at the Persib U-18 Academy in 2024. The method used in this study was the experimental method with the design in this study, namely Pre Experimental Design with a pattern (pre-test, post-test design), and the sampling technique was carried out using the Random assignment technique. Based on the data, there is an increase in VO2Max with the mix group being superior compared to the interval and pyramid groups in the VO2Max variable, but there is no significant difference between the interval and pyramid groups. While for the Teamwork variable, there is an increase in each group but there is no significant difference between each group.